Chemistry Learning Through CIRC on DNA Base Materials: Hypothesis Testing the Kolmogorov-Smirnov Method on Male and Female Population Samples - Tri Susdarwono, Endro (Yayasan Nurul Yakin Bunga Tanjung, 2022)
Cooperative Integrated Reading and Composition (CIRC) is one type of cooperative learning model that combines reading activities with other activities, such as writing, discussion, and presentation in an integrated manner. The purpose of this study is to provide a description of learning chemistry through CIRC on DNA base material. The method used in this research is experimental research. The characteristics of experimental research in this study include manipulation, control or control, and observation. The research design used is the one-shot case study design, while the sampling technique used for this design is purposive sampling. The research hypothesis testing procedure used the Kolmogorov-Smirnov method for multiple sample groups. Based on the comparison between the D value in the table and the calculated D value, the D value is 0.142857. This value is smaller than the D value in the table of 0.726951. Thus, the null hypothesis which states that the post-test score category for male students is the same as the post-test score category for female students. In this condition, it can be concluded that Chemistry Learning Through CIRC on DNA Base Material for students of different sexes produces the same category of posttest scores. This means that this learning can be applied to male and female students equally well.